2010
DOI: 10.1021/ie100065m
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability and Isomerization Mechanism of exo-Tetrahydrodicyclopentadiene: Experimental Study and Molecular Modeling

Abstract: Thermal stability and the primary initiation mechanism of exo-tetrahydrodicyclopentadiene (exo-THDCP, C10H16) were investigated in a batch-type reactor. The catalytic role of the stainless steel inside the reactor was eliminated by inserting a quartz flask. exo-THDCP decomposed at temperatures over 623 K and 1-cyclopentylcyclopentene (1-CPCP, C10H16) and 4-methyl-2,3,4,5,6,7-hexahydro-1H-indene (4-MHI, C10H16) were the primary decomposition products of exo-THDCP. C10 hydrocarbons were determined to be the majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 19 publications
2
31
0
Order By: Relevance
“…Generally, there are many components in the liquid residuals as a result of its cracking. In the light fractions, C5-C6 products of cycloalkenes and aromatics are observed, whereas a little amount of polycyclic aromatic hydrocarbons are also observed, which agrees well with the results reported in the literature [36][37][38][39][40][41].…”
Section: Quasi-homogenous Catalytic Cracking Of Jp-10supporting
confidence: 93%
“…Generally, there are many components in the liquid residuals as a result of its cracking. In the light fractions, C5-C6 products of cycloalkenes and aromatics are observed, whereas a little amount of polycyclic aromatic hydrocarbons are also observed, which agrees well with the results reported in the literature [36][37][38][39][40][41].…”
Section: Quasi-homogenous Catalytic Cracking Of Jp-10supporting
confidence: 93%
“…10,22 Overall, the pyrolysis of JP-10 was found to be mostly efficient at temperatures exceeding 873 K due to the high activation energies of at least 397 kJ mol −1 to cleave the carbon−hydrogen bond(s) (Scheme 2). 10,[14][15][16][17]20,21 Distinct catalysts have been proposed to decrease the activation energy in the decomposition of JP-10. Li et al 27 explored the effects of gold nanoparticles, but the improvement of the cracking rate of JP-10 only achieved 10% with the dispersion stability of metal nanoparticles, limiting the use as a catalyst in JP-10 decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decades, researchers exploited a great variety of approaches to study the thermal decomposition and oxidation of JP-10 such as distinct reactor types (flow tube, jet stirred, and batch), , shock tubes, ,, and high-temperature chemical reactors (Table ) with identified products compiled in Table S1. ,, The majority of these products were reported in a chemical microreactor setup by Zhao et al by exploiting vacuum ultraviolet photoionization detection along with studies by Johnson et al, Pan et al, and Huang et al Electronic structure calculations by Morozov et al provided a theoretical framework of these findings and yielded in-depth mechanistical insights into the feasible pathways, leading to the pyrolysis products of JP-10. These studies revealed that the decomposition of JP-10 is initiated by distinct C–H bond cleavages ,, followed by C–C bond β-scissions via biradical intermediates; these pathways are consistent with the cleavage of strained C–C bonds eventually initiating the unimolecular decomposition of the carbon skeleton of JP-10 (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Air-breathing propulsion systems rely on the combustion of hydrocarbon fuels such as of Jet Propellant-10 (JP-10). , The exo -tetrahydrodicyclopentadiene molecule (C 10 H 16 ; Scheme ) represents the major component of JP-10 and is defined by a high volumetric energy (39.6 kJ cm –3 ) due to three five-membered ring moieties incorporated into a single molecule along with the inherent ring strain energy. This makes JP-10 not only an attractive fuel for missiles, pulse-detonation engines, and ramjets ,, but also interesting for the physical (organic) chemistry, combustion, and theoretical chemistry communities to explore its decomposition and oxidation experimentally, theoretically, and in combustion models. Exploiting shock tubes, flow tubes, , and high-temperature chemical reactors, ,, a detailed understanding of the decomposition of pure JP-10 is beginning to emerge. The unimolecular decomposition (“pyrolysis”) of JP-10 leads to smaller hydrocarbon molecules and reactive transient species, among them aliphatic radicals, resonantly stabilized free radicals (RSFRs), and aromatic radicals (ARs), , which initiate the complex chemistry in the oxidation of JP-10 based jet fuel.…”
mentioning
confidence: 99%